On distance Laplacian spectrum of zero divisor graphs of the ring Z_n - Pirzada, S.; Rather, B.A.; Chishti, T.A. (Carpathian Mathematical Publications, 2021)
For a finite commutative ring Z_n with identity 1 eq 0, the zero divisor graph Γ(Z_n) is a simple connected graph having vertex set as the set of non-zero zero divisors, where two vertices x and y are adjacent if and only if xy=0. We find the distance Laplacian spectrum of the zero divisor graphs Γ(Z_n) for different values of n. Also, we obtain the distance Laplacian spectrum of Γ(Z_n) for n=p^z, z≥ 2, in terms of the Laplacian spectrum. As a consequence, we determine those n for which zero divisor graph Γ(Z_n) is distance Laplacian integral.